Hubungan Aktivitas Komunikasi dengan Tingkat Keberdayaan Kader Posdaya di Kota dan Kabupaten Bogor - Sigit Pamungkas; Amiruddin Saleh; Pudji Muljono (Institut Pertanian Bogor, 2013)
Abstract Posdaya is an integrated forum of friendship, communication, advocacy, and family empowerment. Posdaya focuses on four fields, namely education, health, entrepreneurship and environment. The study was administered using a descriptive correlational research survey design by scrutinizing communication activities and level of empowerment. The purposes of this study were: 1) to describe the communication activities of Posdaya cadres in Bogor City and Bogor Regency; 2) to describe the empowerment level of Posdaya cadres in Bogor City and Bogor Regency; 3) to analyze the individual characteristics and environmental factors associated with communication activities of Posdaya cadres in Bogor City and Bogor Regency; 4) to analyze the individual characteristics and environmental factors associated with the level of empowerment of Posdaya cadres in Bogor City and Bogor Regency; and 5) to analyze the relationship between the communication activities and level of empowerment of Posdaya cadres in Bogor City and Bogor Regency. The samples of this study were 92 Posdaya cadres. The data was processed and analyzed using t-test samples and rank Spearman Correlation Formula. The results showed that: 1) there is a difference in terms of level of education, level of experience, level of income, access to media, and the role as companion between the cadres in Bogor City and Bogor Regency; 2) there is a difference on the use of communication media such as radio and television between the cadres in Bogor City and Bogor Regency; 3) there is a relation in terms of cognitive, affective and behavior aspects between interpersonal activities, mediated communication, and communication in groups and level of empowerment of Posdaya cadres. Keywords: communication activities, posdaya cadres, empowerment